PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Iwan Ridwan; Shela Apriana (Universitas La Tansa Mashiro, 2019)
The development of business in Indonesia has now begun to rampant and develop very rapidly one of them is cosmetic business. Each company competes with each other in pursuit of profit. The development of the Times and technology makes the needs of the people of beauty tools also increase and it becomes a necessity of society today. It is evidenced in the data obtained by CCI-Indonesia in 2010-2015 where the beauty and personal care industry in Indonesia grew rapidly from year to time. The purpose of this research is to know the influence of brand image and product quality to the decision of purchase of Wardah products in the shop Putra Segar cosmetics in Rangkasbitung.The research method used is descriptive method using a quantitative approach, i.e. to explain a problem based on the data in the form of figures (statistical data). The population used in this study is that consumers visit the store fresh cosmetics son with 18.599 the number of visitors, using the formula error level slovin 10% then the sampael obtained as many as 99 consumers. The technique of data collection is the study of librarianship and the questionnaire. Data analysis technique used is multiple regression analysis, correlation analysis, multiple coefficient of determination, t-test and f-test.Based on the research conducted, obtained test results t that brand image (X 1), namely the significant level of significant extent < (0.026 < 0.05). So starting in H0 and Ha accepted and significant value of the obtained product quality (X 2), namely the significant level of significant extent < (0.000 < 0.05). So starting in H0 and Ha is received. That means there are influences between the brand image Of the products purchase at Wardah and there is the influence between product quality Of Product purchases at Wardah. As well as the results of hypothesis testing the F value obtained significant i.e. 0.000 value smaller than 0.05 significant level. Or F-count is greater than the F-table (0, 13650> 0, 309). Then it can be inferred that the brand image and product quality influence on purchasing decisions simultaneously.